2013
DOI: 10.3989/gya.084412
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-catalyzed glycerolysis of fish oil to obtain diacylglycerols

Abstract: RESUMEN Glicerolisis de aceite de pescado catalizada por lipasa para producir diacilglicéridosDiacilglicéridos (DAG) ricos en n-3 fueron producidos en la glicerolisis de aceite de pescado rico en n-3 PUFA catalizada por Novozym 435. Las agitaciones orbital y magnética fueron evaluadas con el propósito de minimizar las limitaciones de transferencia de masa y garantizar la homogeneidad de la mezcla de reactivos. Diferentes temperaturas (65, 70, 75, 80, 85 y 90 °C) y velocidades de agitación (300, 500, 700 y 900 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Generally, MAG and DAG are used as additives in food production systems, or can also be an emulsifier for food, cosmetics, and medicine [49]- [51]. DAG-rich oils have been widely studied as an alternative to TAG-based oils to inhibit fat accumulation and reduce the level of postprandial TAG in the blood [52]. DAG-rich oils have higher melting points than TAG-based oils, even though their fatty acid composition is almost the same [53].…”
Section: Monoacylglycerolanddiacylglycerolmentioning
confidence: 99%
“…Generally, MAG and DAG are used as additives in food production systems, or can also be an emulsifier for food, cosmetics, and medicine [49]- [51]. DAG-rich oils have been widely studied as an alternative to TAG-based oils to inhibit fat accumulation and reduce the level of postprandial TAG in the blood [52]. DAG-rich oils have higher melting points than TAG-based oils, even though their fatty acid composition is almost the same [53].…”
Section: Monoacylglycerolanddiacylglycerolmentioning
confidence: 99%
“…Using immobilized enzymes in glycerolysis offers additional benefits including greater enzyme stability and the elimination of enzyme recovery and purification steps [27,28]. Previous studies have found immobilized enzymes are effective for both vegetable and fish oil esterification reactions, with the enzyme remaining active over multiple cycles [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Das and Ghosh (2019) compared two synthesis ways to prepare MCD (C 8 -DAG) using enzyme and chemical catalysts both under solvent-free conditions using a stirred tank reactor and obtained DAG yields of 58 and 53% when catalyzed by RM IM and Novozym R 435, respectively. However, it has been reported that the preparation of DAG via esterification using mechanical stirring were not encouraged attributed to the viscous and immiscible state of substrate mixtures (Baeza-Jiménez et al, 2013). This could be a contributing factor for the long reaction time (RM IM, 18 h and Novozym R 435, 6 h) needed for the esterification synthesis of C 8 -DAG by Das and Ghosh (2019).…”
Section: Introductionmentioning
confidence: 99%